Textbook Readibility Assessment of K13 English Textbook For Twelfth Grade - Susilo Adi Perwira (IJET (Indonesian Journal of English Teaching), 2019)
English textbook for twelfth grade of SMA which is published by Ministry of Education and Culture is a compulsory textbook which is based on national curriculum 2013 to support education in Indonesia. This study aims to investigate the readability level of the English textbook. It uses descriptive quantitative method to examine the readability of this book. The data are in the form of texts derives from transactional and interpersonal text, short functional text, reading text, instructional text inside the book. There are 180 data taken from those four texts. They are analyzed by using Miyazaki EFL readability formulae as a tool to measure the readability level whether it is suitable or not for twelfth grade students. According to Miyazaki EFL readability test, the easiest text from the book is in 5th grade and the hardest one is in post-school/university grade. But the most frequent grade appear in this book is in 8th and 9th grade which is 77 data (texts). The average of this book score is 63.2 which means it is suitable for 8th and 9th grade. This book is too easy for twelfth grade according to Miyazaki EFL readability test.